A robust 3D zinc(ii)–organic framework for efficient dual detection of acetylacetone and Tb3+ ions. Issue 29 (7th July 2021) - Fu, Miao-Miao; Fu, Lianshe; Cui, Guang-Hua
Abstract : A fluorescent Zn(ii ) MOF with a new 3D pillared framework was synthesized and characterized, which displays excellent stability, high sensitivity and selectivity for sensing of acac and Tb 3+ ions through fluorescence quenching and enhancement effects, respectively. Abstract : There has been broad attention to the recognition and detection of ions and organic small molecules due to their essential roles in environmental systems. However, dual-functional probes have seldom been developed for sensing organic constituents and lanthanide ions. A new 3D pillared Zn(ii )−organic framework [Zn3 (L)(DCTP)3 ] n (1 ) (L = 1, 4-di(1 H -benzo[ d ]imidazol-2-yl)butane and H2 DCTP = 2, 5-dichloroterephthalic acid) was hydrothermally synthesized and structurally characterized, and features a unique 3D 4, 4, 4, 6-connected framework containing approximately 9.99 × 9.78 Å 2 cubic channels. 1 displays excellent thermal and pH stability and can act as a novel "turn-on" fluorescent probe for highly selectively sensitizing Tb 3+ ions through an "antenna effect". Furthermore, 1 is a dual-response fluorescent sensor for monitoring acetylacetone and Tb 3+ ions with rapid response times (within 1 min), low limits of detection (LOD) (5.02 × 10 −6 /1.15 × 10 −8 M, separately) and great anti-interference ability and recyclability towards the analytes. The related sensing mechanisms for detecting analytes are also investigated in detail.